The Hsa_circ_0091579/miR-940/TACR1 Axis Regulates the Development of Hepatocellular Carcinoma - Jiang, Peiqiang (Cancer Manag Res, 2020)
PURPOSE: Circular RNAs (circRNAs) play important roles in hepatocellular carcinoma (HCC) development. The circRNA hsa_circ_0091579 (circ_0091579) is dysregulated in HCC, while the mechanism of circ_0091579 in HCC development is largely unknown. PATIENTS AND METHODS: Thirty paired cancer and adjacent normal tissues were harvested from HCC patients. SNU-387 and Huh7 cells were cultured in this study. circ_0091579, microRNA-940 (miR-940) and tachykinin-1 receptor (TACR1) abundances were measured via quantitative reverse transcription-polymerase chain reaction or Western blot. Cell viability, migration, invasion, colony ability, cell cycle distribution and apoptosis were assessed via 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide, transwell assay, colony formation assay and flow cytometry. The interaction among circ_0091579, miR-940 and TACR1 was tested via dual-luciferase reporter analysis. The anti-HCC role of circ_0091579 knockdown in vivo was investigated using xenograft model. RESULTS: circ_0091579 expression was enhanced in HCC tissue samples and cells. circ_0091579 silence inhibited cell viability, migration, invasion and colony formation, induced cell cycle arrest at G0/G1 phase, and promoted apoptosis in HCC cells. miR-940 was targeted via circ_0091579 and miR-940 knockdown reversed the suppressive effect of circ_0091579 silence on HCC development. miR-940 targeted TACR1 to repress HCC development. circ_0091579 could regulate TACR1 expression by mediating miR-940. Down-regulation of circ_0091579 decreased xenograft tumor growth. CONCLUSION: Knockdown of circ_0091579 repressed HCC development by mediating miR-940/TACR1 axis, indicating a new pathogenesis of HCC.